Impacts of ε‐polylysine hydrochloride with thymol on biogenic amines formation and biochemical changes of squid (Illexargentinus). Issue 6 (20th April 2021) - Li, Yingchang; Cui, Lei; Du, Fengxia; Han, Xiao; Li, Jianrong
Abstract: The effect of ε‐polylysine hydrochloride (ε‐PL) and thymol (TY) in the changes of biogenic amines (BAs) and the quality properties of Illex argentinus was evaluated by measuring the content of BAs, total viable count (TVC), pH, sensory score, and odor change. The experiment was divided into four groups, the control, ε‐PL, TY, and the compound (ε‐PL–TY) group. The results showed BAs‐producing bacteria contained Enterobacteriaceae bacterium, Citrobacter braakii, Klebsiella pneumoniae, Obesumbacterium proteus, Hafnia alvei, Hafnia paralvei, and Hafnia alvei sensu. ε‐PL, TY, and ε‐PL–TY effectively inhibited the increase of BAs content, TBA, pH, and maintained the fresh flavor and sensory properties. ε‐PL–TY was the best to reduce the content of phenethylamine, putrescine, cadaverine, and tyramine by 45.11%, 79.08%, 72.92%, and 63.53% compared with the control at the end of storage. ε‐PL–TY was a promising BAs inhibitor that could protect the edible value and safety of aquatic products. Practical applications: Illex argentinus is susceptible to corruption, and then microorganism in Illex argentinus will produce several biogenic amines, while the combined preservative is the most convenient way to protect its quality after postmortem. Although ε‐polylysine hydrochloride has a better antibacterial activity as a preservative, the single preservative cannot exert a better effect. Thymol is a natural plant ingredient with great antioxidant properties and antibacterial activities, which had an inhibitory synergy with ε‐PL in this study. ε‐polylysine hydrochloride– thymol could be a promising preservative to control the biochemistry activities and protect the edible value of squid.